Increasing Safety Awareness as an Effort to Build Preparedness in Disaster-Prone Schools - Widowati, Evi; Wahyuningsih, Anik Setyo; Muzaqi, Lutfi; Sulistyani, Ummi Nur Laila; Rahma, Fitra Aulia; Putri, Risa Anggita; Febriananda, Hanif Satria (Universitas Negeri Semarang, 2025)
Geologically, Indonesia is located at the confluence of three large plates: Indo-Australian, Eurasian, and Pacific. It passes through two of the world's main volcanic routes, making it a disaster-prone area. As a result, Indonesia has many active volcanoes, including Mount Merapi. In disaster conditions, students are a vulnerable group, both physically and psychosocially, due to disruption to the learning process and potential trauma. Efforts to increase preparedness through implementing the sister school program, namely cooperation between affected and buffer schools, are urgently needed. However, the implementation of this program in Magelang Regency is still not optimal, especially in its integration into the sister village program, so that vulnerability to disasters during school hours remains high. The solution implemented is to help schools increase their preparedness capacity. The results showed increased participants' understanding of the concepts, benefits and roles of buffer and affected schools in the disaster mitigation framework. Therefore, efforts are still needed to develop affected and buffer schools integrated into disaster-resilient villages.